A qualitative exploration of barriers to the utilisation of outpatient healthcare services among older persons in the Ho Municipality of Volta Region of Ghana - Peter Adatara; Philemon Adoliwine Amooba (Elsevier, 2021)
Background: Ghana government has introduced the National Health Insurance Scheme which exempted older adults from paying for outpatient and others healthcare services. However, reports from healthcare facilities in Ho Municipality showed that older adults do not utilise healthcare services from healthcare facilities when they are sick. Objective: The objective of this study was to explore the barriers to the utilisation of healthcare services among older persons in the Ho Municipality in the Volta Region of Ghana. Methods: A qualitative study using semi-structured interviews were used to explore the barriers to utilisation of outpatient healthcare services among older persons. The interviews were carried out with a total of twelve older persons between the ages of 60 and 80 years who did not use healthcare services. Participants' views on the barriers to the utilisation of outpatient services were analysed thematically. Results: This study found the following as barriers: Financial constraints and high costs of healthcare services; geographical inaccessibility to healthcare; older people lacked family caregivers to support them in accessing healthcare; older persons did not utilise healthcare services due to bad attitudes of health staff. Conclusion: This qualitative study provided useful insight into the barriers to the utilisation of healthcare services among older persons in Ghana similar to other developing countries. It showed that older persons encounter many barriers which prevented them from utilising outpatient healthcare services. There is the need for the government of Ghana and other stakeholders to address the challenges to facilitate utilisation of healthcare services among older persons for better outcomes.